How D.N.C. Warded Off Hacks in 2020. - PERLROTH, NICOLE (New York Times, 2021)
The article discusses the cybersecurity strategies reinforced by Democratic National Convention (DNC) chief information security officer Bob Lord to protect the 2020 DNC against cyberattacks.